Efektywność nauczania we wrocławskich liceach - Ejsmont, Wiktor (Efficiency of teaching at high schools in Wroclaw, 2009)
The article focuses on measuring the effectiveness of education of the Polish language in secondary schools in Wrocław. In the first part of the article the author appro-priately converts the data and explains the construction of models with random factors used by Aitkins and Longford. In the second part of article it applies those data to the proper models and draw conclusions from the results obtained
Didactics of Mathematics, 2009, Nr 5-6 (9-10), s. 111-128
Keywords: school effectiveness; teaching; analysis of panel data